2016
DOI: 10.1080/09593330.2016.1173118
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of dewatering characteristics by co-digestion of rice straw with sewage sludge

Abstract: A continuous mesophilic co-digestion of sewage sludge and softened rice straw was conducted and the dewatering characteristics of digested sludge were evaluated by a dewatering experiment using a belt press. The digestion was operated with solid retention time (SRT) of 25 days, and the feeding ratio of sludge to rice straw was 1:0.5 (total solids base). After 129 days of stable operation, the properties of digested sludge were analysed; then five kinds of cationic coagulants were tested to select the optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Methane (CH 4 ) yields of each substrate are summarized in Table 1, CH 4 of Run 2 was calculated using the data after pH adjustment, and CH 4 yield of RS in Run 3 was calculated assuming that the degradation of sludge was the same as that in Run 1. Average CH 4 yields of raw sludge and RS were estimated as 0.31 and 0.26 L/g-TS, respectively, and the results were in accordance with the authors' previous study [8], suggesting that the digestion was conducted stably in the present study. CH 4 yield of each substrate was also summarized on COD Cr base ( Table 1).…”
Section: Continuous Co-digestion Experiments Reactor Performance Figursupporting
confidence: 92%
See 2 more Smart Citations
“…Methane (CH 4 ) yields of each substrate are summarized in Table 1, CH 4 of Run 2 was calculated using the data after pH adjustment, and CH 4 yield of RS in Run 3 was calculated assuming that the degradation of sludge was the same as that in Run 1. Average CH 4 yields of raw sludge and RS were estimated as 0.31 and 0.26 L/g-TS, respectively, and the results were in accordance with the authors' previous study [8], suggesting that the digestion was conducted stably in the present study. CH 4 yield of each substrate was also summarized on COD Cr base ( Table 1).…”
Section: Continuous Co-digestion Experiments Reactor Performance Figursupporting
confidence: 92%
“…It is suggested that due to the high C/N ratio of RS, the organic acids are generated as intermediates of carbohydrates degradation, and further accumulate and lead to the decrease of pH. On the other hand, the results of methane production, TS, VS removal rates of sludge digestion (Run 1) and the co-digestion (Run 3) were in accordance with the results in our previous study [8]. Table 2 shows the average concentrations of DOC, soluble COD Cr , carbohydrates, proteins, humic matter, acetate and propionate in the digested sludge of each reactor.…”
Section: Continuous Co-digestion Experiments Reactor Performance Figursupporting
confidence: 89%
See 1 more Smart Citation